The Influence of Globalization on Customary Legal Systems: A Review from an Archipelago Perspective - Firayani (Leges Privatae, 2024)
This article examines the impact of globalization on customary law systems in the archipelago, focusing on changes that occur in the structure and practice of customary law amidst the flow of modernization. Globalization has brought various significant impacts on customary law, both in positive and negative aspects. This study uses literature study and case analysis methods to evaluate how customary law adapts to or is affected by global trends. The results show that globalization affects customary law in various ways: from adjustments to international legal practices to challenges in maintaining local cultural identity. The author also notes that although globalization brings opportunities for the protection and recognition of customary rights through international cooperation, this is often accompanied by pressure to align customary norms with global standards that may not always be in accordance with local values. This article suggests the need for a balanced approach between maintaining the richness of customary law and adapting to global developments to ensure the sustainability of customary law systems in the archipelago.